3D Printing in Breast Reconstruction: From Bench to Bed - Mu, Xingdou; Zhang, Juliang; Jiang, Yue (Frontiers in Surgery, 2021)
Surgical management of breast cancer often results in the absence of the breast. However, existing breast reconstruction methods may not meet the need for replacement tissue. Tissue engineering with the use of emerging materials offers the promise of generating appropriate replacements. Three-dimensional (3D) printing technology has seen significantly increased interest and application in medically-related fields in recent years. This has been especially true in complex medical situations particularly when abnormal or complicated anatomical surgical considerations or precise reconstructive procedures are contemplated. In addition，3D bio-printing which combines cells with bio-material scaffolds offers an exciting technology with significant applications in the field of tissue engineering. The purpose of this manuscript was to review a number of studies in which 3D printing technology has been used in breast reconstructive surgical procedures, and future directions and applications of 3D bio-printing.